14 states, 22 senators, 59 representatives & the writing of the establishment clause: an analysis of the original intent - Foust, Joseph R. (Kansas State University, 2010)
This rhetorical history study attempts to refocus the narrow debate on the concept of the “Separation of Church and State.” Most scholars and popular organizations primarily focus their determination of the original intent of the Establishment Clause on the views of James Madison, Thomas Jefferson, and Virginia. However, according to the United States Constitution it takes three-fourths of the states and two-thirds of Congress to ratify an amendment. As a result, most arguments on this topic center on an extremely small minority of evidence: one of fourteen states, and only one of eighty-one members of Congress to determine the Founders’ original intent. This study reverses this trend and consults evidence from all the states involved as well as the records of Congress. Since comparable documents are vital to understanding history, all the state constitutions, state bills of rights, and state proposed amendments to the Federal Constitution are consulted as evidence at the beginning of this study. Additionally, every reference of religion in the above documents are individually presented in order to alleviate concerns of potential evidence manipulation. Further, the debates in Congress and the multiple drafts of the Establishment Clause are evaluated in the process of determining the Founders’ original intent. Throughout the study, several useful tables have been constructed in order to facilitate the processing and evaluation of such a large base of evidence. The results of this study indicate a lack of evidence for the contemporary view that the Founders’ intent was to create a total separation between church and state. From the specific religious concerns voiced in the state ratification debates of the Constitution, what religious limits were written into state constitutions/bills of rights, and the amendments that states proposed concerning religion; it becomes evident that the Founders’ intention was only to prevent a particular Christian denomination from becoming the established "National American Church.”
Fourteen states, twenty two senators, fifty nine representatives and the writing of the establishment clause: an analysis of the original intent
Keywords: Establishment Clause; Separation of church and state; Bill of Rights; First Amendment; Constitution; Religion and government; Founding Fathers; History, United States (0337)